Rhetoric and Persuasion from the Classical Era Through the Modern Age - MEDJEDOUB, Rima (Milev Journal of Research and Studies, 2017)
Rhetoric is the art of persuasion. The rhetorical theory offers a method for discovering the means of persuasion in discourse. Since the classical period up to the introduction of the new rhetoric, the views and perceptions have altered immensely in a myriad of ways. Consequently, I suggest, in order to overcome the complexity of understanding the rhetorical theory and its application, to go through the rhetoric’s history which has always been focused on areas pertinent to persuasion. In this overview, I avoided to deal with the contemporary theories (and leave them to another occasion) because in the turn of the twentieth century, the new rhetoric broke down with the old tradition, the emphasis on persuasion, and new meanings and theories have promulgated in a quantity and audacity unprecedented in the history of rhetoric that the scope of the present article does not allow to cover.